2017
DOI: 10.1080/14737175.2017.1283217
|View full text |Cite
|
Sign up to set email alerts
|

Investigational drugs in recent clinical trials for treatment-resistant depression

Abstract: Introduction The authors describe the medications for treatment-resistant depression (TRD) in phase II/III of clinical development in the EU and USA and provide an opinion on how current treatment can be improved in the near future. Areas covered Sixty-two trials were identified in US and EU clinical trial registries that included six investigational compounds in recent phase III development and 12 others in recent phase II clinical trials. Glutamatergic agents have been the focus of many studies. A single i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 126 publications
(245 reference statements)
0
45
0
2
Order By: Relevance
“…14,15 The observation that a single intravenous dose of glutamatergic modulator ketamine produces a robust and rapid AD effect was a turning point that opened the way for other, more selective glutamatergic modulators (intranasal esketamine, rapastinel). 16 …”
Section: Ketaminementioning
confidence: 99%
“…14,15 The observation that a single intravenous dose of glutamatergic modulator ketamine produces a robust and rapid AD effect was a turning point that opened the way for other, more selective glutamatergic modulators (intranasal esketamine, rapastinel). 16 …”
Section: Ketaminementioning
confidence: 99%
“…In 2000, a pilot study reported that intravenous infusion of a subanesthetic dose (0.5 mg/kg) of the NMDAR antagonist ketamine (0.5 mg/kg) produced a rapid and robust antidepressant effect in patients with depression [2]. These observations raised the possibility of an alternative to available biogenic amine-based antide pressants that often take weeks to months to produce a clinically meaningful therapeutic effect, leaving patients at increased risk of suicide [1,3,4]. …”
mentioning
confidence: 99%
“…Between 15% and 30% of patients who have a major depressive disorder (MDD) do not respond satisfactorily to two successive courses of antidepressant treatment (‘treatment-resistant depression’;TRD) [1,3,4]. In 2006, a randomized controlled trial (RCT) conducted by the National Institute of Health (NIH) [5] clearly demonstrated a rapid and robust effect of subanesthetic ketamine in TRD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Even though it did not capture clinical interest, the hypothesis of Rook et al [1] deserves to be revisited because relapse is common in MDD and at least 15%-30% of patients with MDD are resistant to treatment, resulting in considerable morbidity and increased risk of suicidal behavior [3]. A vaccine can prevent episodes of MDD, as well as being safe and well tolerated in the long term.…”
Section: Introductionmentioning
confidence: 99%